Effects of teaching and voice rest on acoustic voice charateristics of female primary school teachers - Rajasudhakar R; Savithri S R (Journal of All India Institute of Speech and Hearing, 2010)
Voice problems are known to be the most common among voice professionals worldwide. Teachers form a large group of voice professionals where females are a majority in that profession and are known to have more voice problems than males. The present study investigated the short-term effects of teaching (vocal loading) on acoustic parameters like mean fundamental frequency of phonation (pF0), standard deviation of fundamental frequency of phonation (SD pF0), speaking/reading fundamental frequency (sF0), frequency and amplitude perturbation (jitter and shimmer) and harmonic-to-noise ratio (HNR). Also, the study examined the effect of vocal rest following a workday teaching performance on these parameters. Twelve female primary school teachers in the age range of 23 to 42 years participated in the study whose average professional teaching experience was 8.6 years. The teachers were instructed to phonate vowel /a/ for 8-10 seconds at their comfortable pitch and loudness and read a standard reading passage in Kannada. These recordings were made at three different time intervals - i.e., (a) Monday morning (5-10 minutes prior to starting of teaching) - condition 1, (b) Monday evening (5-10 minutes after the school hours) - condition 2, and (c) Tuesday morning (after 17-18 hours of voice rest) - condition 3. The light-weight, portable digital audio tape (DAT) recorder was used to collect the voice and speech sample. The pF0, SD pF0, perturbation measures like jitter and shimmer and HNR were extracted from phonation of vowel /a/ and sF0 was measured from the reading sample by using PRAAT software. Results revealed that the difference between the acoustic values between condition 1 and 2 were, 14 Hz (pF0), 0.4 Hz (SD pF0), 7 Hz (sF0), 0.2% (jitter), 2.36% (shimmer) and 0.12 dB (HNR). Except HNR, all other vocal parameters increased after teaching performance (condition 2) and recovered back to baseline after 17-18 hours of voice rest (condition 3). The results indicated that these acoustic parameters (except HNR) were sensitive enough to document the extent to which the voice changes occurred due to vocal loading. Also, these altered vocal parameters were transient which recovered back to baseline after adequate voice rest.